1994
DOI: 10.1093/ndt/9.10.1443
|View full text |Cite
|
Sign up to set email alerts
|

Ten years experience of CAPD in diabetics: comparison of results with non-diabetics

Abstract: CAPD outcomes were compared between a group of 301 diabetic patients (mean age +/- SD, 58.9 +/- 12.7 years, 55.8% males) and a group of 1689 non-diabetic patients (mean age +/- SD 57.8 +/- 14.8 years, 55.9% males) treated in 30 centres participating in the Italian Cooperative Peritoneal Dialysis Study Group from 1980 to 1989, with follow-up observation periods of 444 years (mean +/- SD, 1.48 +/- 1.24) and of 3502 years (mean +/- SD, 2.07 +/- 1.91) respectively. CAPD was the first modality for 87.2% of diabetic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
34
0
3

Year Published

1998
1998
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(43 citation statements)
references
References 0 publications
6
34
0
3
Order By: Relevance
“…In other studies, it has been reported that diabetes mellitus is not a risk factor for peritonitis in PD patients. [11][12][13] In terms of time elapsed on peritoneal dialysis, there was no difference between the three groups. In some studies, time elapsed on PD is shown to have a significant impact on peritonitis frequency, [2,14] but in our study it showed no effect.…”
Section: Discussionmentioning
confidence: 99%
“…In other studies, it has been reported that diabetes mellitus is not a risk factor for peritonitis in PD patients. [11][12][13] In terms of time elapsed on peritoneal dialysis, there was no difference between the three groups. In some studies, time elapsed on PD is shown to have a significant impact on peritonitis frequency, [2,14] but in our study it showed no effect.…”
Section: Discussionmentioning
confidence: 99%
“…[5] It is known that diabetes is accompanied by multi-system and organ dysfunction, and serious questions have been raised about the outcomes (survival, morbidity) in this group of patients, in particular the impact of treatment on their quality of life. [1,6,7] There are many studies of quality of life in ESRD patients, but a limited number in patients with diabetes. [1] In the absence of prospective and longitudinal studies, quality of life in diabetic CAPD patients has only partly been examined by assessing co-morbid factors and survival, using mainly generic instruments.…”
Section: Introductionmentioning
confidence: 99%
“…Este peor pronóstico, aparece en todas las modalidades de TSFR: HD (10,20); DPCA (21,22) y trasplante renal (9,10). Los pacientes diabéticos no sólo tienen una mortalidad mayor sino que además, su morbilidad es muy alta.…”
Section: Resultsunclassified
“…Durante años, muchos nefrólogos apostaban por la diálisis peritoneal continua ambulatoria (DPCA) como el tratamiento sustitutivo de elección (12)(13)(14). En la actualidad, existen trabajos que obtienen mejores resultados con las nuevas técnicas de hemodiálisis-hemodiafiltración, y reivindican el papel beneficioso de dichos tratamientos (15). Los criterios de selección utilizados en los diabéticos para considerarlos candidatos a trasplante renal se han ampliado en los últimos años, aunque siguen sin estar totalmente claros (6,16,17).…”
Section: Introductionunclassified